Scaling effects of a novel solar receiver for a micro gas-turbine based solar dish system. (1st March 2018) - Aichmayer, Lukas; Garrido, Jorge; Laumert, Björn
Highlights: Receiver scaling effects analyzed between full-scale system and solar simulator. Ray-tracing routines established and validated against measurement data. Detailed numerical model of volumetric solar receiver established. Multi-objective optimization used to identify suitable receiver configurations. Solar receiver configuration identified that yields representative results. Abstract: Laboratory-scale component testing in dedicated high-flux solar simulators is a crucial step in the development and scale-up of concentrating solar power plants. Due to different radiative boundary conditions available in high-flux solar simulators and full-scale power plants the temperature and stress profiles inside the investigated receivers differ between these two testing platforms. The main objective of this work is to present a systematic scaling methodology for solar receivers to guarantee that experiments performed in the controlled environment of high-flux solar simulators yield representative results when compared to full-scale tests. In this work the effects of scaling a solar air receiver from the integration into the OMSoP full-scale micro gas-turbine based solar dish system to the KTH high-flux solar simulator are investigated. Therefore, Monte Carlo ray-tracing routines of the solar dish concentrator and the solar simulator are developed and validated against experimental characterization results. The thermo-mechanical analysis of the solar receiver is based around a coupled CFD/FEM-analysis linked with stochastic heat source calculations in combination with ray-tracing routines. A genetic multi-objective optimization is performed to identify suitable receiver configurations for testing in the solar simulator which yield representative results compared to full-scale tests. The scaling quality is evaluated using a set of performance and scaling indicators. Based on the results a suitable receiver configuration is selected for further investigation and experimental evaluation in the KTH high-flux solar simulator.